Effect of Irrigation System, Pesticide Use, and Human Resource Management on Productivity Growth of Oil Palm in Indonesia - Judijanto, Loso; Yumhi, Yumhi; Lesmana, Tera (West Science Social and Humanities Studies, 2024)
This study investigates the impact of irrigation systems, pesticide use, and human resource management (HRM) on the productivity growth of oil palm plantations in Indonesia. Utilizing a quantitative approach, data were collected from 120 respondents, representing various plantations, using a Likert scale (1–5). Statistical analysis was conducted using SPSS version 26 to assess the relationships between the independent variables (irrigation systems, pesticide use, and HRM) and the dependent variable (productivity growth). The findings reveal that efficient irrigation practices, responsible pesticide use, and effective HRM significantly contribute to productivity growth. Among these, HRM was found to be the most influential factor. These results highlight the need for plantation managers to prioritize resource management and workforce development to achieve sustainable productivity gains. The study provides valuable insights for enhancing oil palm productivity and promotes the adoption of sustainable practices in Indonesia’s palm oil industry.